Morphophysiological and productivity characteristics in peanut culture in response to biostimulant application - Ribeiro, Vinicius Ferreira; Andrade, Christiano Lima Lobo de; Cabral Filho, Fernando Rodrigues; Vieira, Gustavo Henrique de Oliveira; Leão, Karollyne Ramos; Ferreira, Tarimar Martins; Texeira, Marconi Batista (Brazilian Journal of Science, 2023)
Use of the biostimulant Titan FH® is of great importance because it offers better development for the grain, making it an efficient natural way to help the performance of the plant. Peanut is a plant of the Fabaceae family, genus Arachis, which has many known species, among which, only Arachis hypogaea L. is cultivated. The species is cultivated in several countries around the world, therefore the peanut producing regions have different characteristics in relation to climate and soil type, for this reason it is necessary to use cultivars with more technology that adapt to each condition. This study aimed to analyze the morphophysiological characteristics and productivity along with the effectiveness of the biostimulant reference. The experiment was carried out in the experimental area of the Federal Institute of Education, Science and Technology in the municipality of Rio Verde, Goiás, Brazil. The treatments consisted of different dosages of the biostimulant Titan FH®. The experimental design was randomized blocks, with 3 replications. The plots corresponded to 5 rows of 5 m in length, with 90 cm spacing between rows. In the samplings, the components of gas exchange, biometrics, productive components, and statistical analysis were analyzed. There was no significant difference in photosynthetic and crop growth rates, but it was significant in grain yield.